2012
DOI: 10.1097/mej.0b013e32834d6efb
|View full text |Cite
|
Sign up to set email alerts
|

Performance of illness severity scores to guide disposition of emergency department patients with severe sepsis or septic shock

Abstract: Two-thirds of ED patients with severe sepsis were admitted to the ward, of whom ∼13% clinically deteriorated, resulting in ICU admission and higher mortality. The PIRO score adds little value over clinical judgement in guiding adequate disposition to wards or the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…Two previous studies showed different transfer rates from inpatient wards to ICU level of care (4,14). These mixed results are likely due to institutional protocols as well as differences in the methodological study approach (4,5). In our study, we found female patients to be at higher risk of developing septic shock within 48 hours when compared with male patients.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Two previous studies showed different transfer rates from inpatient wards to ICU level of care (4,14). These mixed results are likely due to institutional protocols as well as differences in the methodological study approach (4,5). In our study, we found female patients to be at higher risk of developing septic shock within 48 hours when compared with male patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Three previous studies sought to evaluate the unanticipated need for ICU transfer in patients diagnosed with sepsis while in the ED (3)(4)(5). However, although it is important to understand unanticipated ICU transfers, admission rates to the ICU are highly variable and physician and/or institution dependent.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Those with lower THERM scores (higher risk) should be considered for referral to critical care, similar to the recommendations for inpatients identified at risk by NEWS. The predisposition, infection, response and organ failure (PIRO) score (a sepsis staging system developed for patients admitted to hospital) has recently been found to add little value over ED clinical judgment in guiding admission to the appropriate level of care,19 and it would be useful to compare THERM with emergency physician judgment, in a future study. THERM could also be used for audit and research, to establish case-mix in a particular ED.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] De Groot et al 24 compared the PIRO and MEDS with physician judgment to predict the need for ICU admission. They found that the PIRO did not perform better than physician judgment in predicting disposition from the ED to a ward bed or to the ICU.…”
Section: Discussionmentioning
confidence: 99%